METHODOLOGY FOR STUDYING THE BIOMEDICAL, SOCIO-ECONOMIC AND DEMOGRAPHIC CHARACTERISTICS OF THE MENTALLY ILL RURAL AND URBAN AREAS (FOR EXAMPLE, PATIENTS WITH NEUROTIC AND SOMATOFORM DISORDERS) - N. A. Kosenko; V. E. Lugovoi; E. A. Pfanenshtil; Y. V. Gridina; V. V. Surikova; V. G. Kosenko; G. V. Lomakina (Кубанский научный медицинский вестник, 2014)
The article presents a map developed by the authors of clinical and social survey of mentally ill in integrated assessment of their quality of life. The card has 52 questions, and depending on their content is driven by 2 to 22 provided responses Double graduation: to disease and during illness. All questions are systematized and grouped into specialized units: biomedical, social, demographic, professional production, logistical and economic characteristics. After statistical analysis of completed cards will identify or supplement the leading causes that contribute to mental illness, and contributing factors affecting the progression of them.